Perencanaan Struktur I Girder dengan Bentang 30 Meter di Desa Dompu - Setiawan, Wira; Winardin, Sofyan; Rahman, M. Deta Zulfikar (Local Engineering, 2026)
The Bridges themselves are classified based on the type of upper structure, one type of bridge upper structure is using prestressed concrete, prestressed concrete is also distinguished based on its cross-sectional profile, namely T, I, T Girder, Box Girder, in this study a comparison was made to see the difference in the upper structure and cost of the bridge with a span of 30.8 meters on the Kandai bridge with the existing upper structure using I Girder and will be compared with T Girder for  obtaining differences in behavior, effectiveness of the structure as well as cost. The research method used is to start by knowing some mass formulationsah, collecting data then planning the load plan for the bridge then modeling on   the SAP2000 software after modeling and getting the force in the next structure analysis to check  the Safety factor  then a cost analysis was carried out and a comparative recap between I and T Girder in the form of differences in the initial condition prestressed force, voltage loss value, service condition pretentension force, final prestressed force and cost presented in the form of a graph. From the results of the calculation analysis, it was concluded that the I Girder is more effective than the T Girder, this is shown by the total volume value of T Girder concrete which is 128,805 m3 and the number of T Girder strands is 355 strands, where the total volume of I Girder concrete is 101,175 m3 and the number of I Girder strands is 235 strands.  This is also evidenced by the I girder safety factor value against the moment, which is 1.141 and against the shear which is 3,59 as needed, compared to the T Girder safety factor against the moment, which is 3,97 and against the shear which is 2.177. The nominal moment produced by the I Girder is 12203,56 kNm and the nominal moment produced by the T Girder is 58221,55 kNm.